ADDRESSING BUDGET ABSORPTION CHALLENGES: CASE STUDY OF KPPN PATI IN SUPPORTING NATIONAL DEVELOPMENT - Aris Saputro; Mujahidah Aristiati; Heni Roviani; Dedi Rahmanto; Harry Z. Soeratin; Suparjito Bin Karnoto (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2025)
This study aims to describe efforts to improve the quality of budget absorption in the work area of the State Treasury Service Office (KPPN) Pati using data from 2023-2024. The method used in this research is a qualitative method by describing the various efforts made to optimize budget absorption and supported by data on the realization of budget absorption. Based on the Budget Implementation Review Report (RPA), the realization of expenditures of Ministries/Institutions (K/L) in the working area KPPN Pati reached Rp833 billion or 98.44 percent of the 2024 budget ceiling allocation and Rp729 billion or 98.49 percent of the 2023 budget ceiling allocation. The challenges in budget absorption include the compatibility between budget plans and implementation, the procurement process of goods and services, and the coordination between stakeholders in budget implementation. Solutions to address these challenges include improvements in aspects of budget planning, optimizing the use of digital systems in budget execution and improving coordination with all stakeholders.